The role of X-ray densitometry in diagnosing calcium metabolism disorders in patients after bariatric surgery - Todurov, I. M.; Kalashnikov, O. O.; Yushchenko, V. P.; Hrynevych, A. A. (Modern medical technology, 2025)
Obesity and bariatric surgery are global medical challenges; however, they are associated with the risk of developing calcium metabolism disorders, which may lead to osteopathies and fractures. Dual-energy X-ray absorptiometry (DXA) plays a key role in the detection of such disorders. Aim: to analyze the role of X-ray densitometry in diagnosing calcium metabolism disorders in patients after bariatric surgery. Materials and methods. A retrospective study was conducted on 31 obese patients after bariatric surgery: sleeve gastrectomy (SG) (n = 14) and biliopancreatic diversion with duodenal switch (BPD-DS) (n = 17). Anthropometric data, levels of ionized calcium, 25(OH)D, and parathyroid hormone (PTH), as well as bone mineral density indicators assessed by DXA, were evaluated. Statistical analysis was performed using SPSS version 23. Results. At an average of 40.7 ± 11.4 months postoperatively, all patients were found to have vitamin D deficiency and secondary hyperparathyroidism. The T-score in the BPD-DS group (-1.77 ± 0.9) was significantly lower than in the SG group (0.47 ± 1.26) (p < 0.001). Osteopathies were more frequently observed after BPD-DS: osteopenia was found in 58.8 % of patients and osteoporosis in 17.6 %. A strong inverse correlation was identified between PTH levels and T-score (rs = -0.71, p = 0.001), highlighting the influence of hyperparathyroidism on the reduction of bone mineral density. Conclusions. DXA is a highly effective method for diagnosing calcium metabolism disorders after bariatric surgery, enabling the detection of early forms of osteopathies. Patients after BPD-DS have a higher risk of osteopenia and osteoporosis compared to patients after SG. X-ray densitometry combined with laboratory monitoring of calcium-phosphorus metabolism should become a standard part of follow-up to ensure timely detection and prevention of complications.